2017
DOI: 10.1007/s00595-017-1483-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of single-incision thoracoscopic surgery using a modified chest wall pulley for primary spontaneous pneumothorax: a propensity score matching analysis

Abstract: The surgical results of mPulLE in patients with PSP with multiple lesions were equivalent to those achieved with three-port VATS under the same conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Other authors have used different devices such as a mini loop retractor, 11 a percutaneous hookwire, 12 or pulled traction threads to lift the target lesion without the need for a grasper. 13 In this way, the port accommodates only 2 instruments at any one time instead of three, which theoretically reduces the risk of collision between surgical instruments and the length of the port incision. However, none of these strategies has yet come into widespread use because they need more expensive devices and/or particular technical skills to lift the lesion in the loop retractor or to suture the parietal pleura from the thoracic cavity with a chest wall pulley.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have used different devices such as a mini loop retractor, 11 a percutaneous hookwire, 12 or pulled traction threads to lift the target lesion without the need for a grasper. 13 In this way, the port accommodates only 2 instruments at any one time instead of three, which theoretically reduces the risk of collision between surgical instruments and the length of the port incision. However, none of these strategies has yet come into widespread use because they need more expensive devices and/or particular technical skills to lift the lesion in the loop retractor or to suture the parietal pleura from the thoracic cavity with a chest wall pulley.…”
Section: Discussionmentioning
confidence: 99%
“…Gentle extrathoracic manipulation of the suture lifts the lesion and creates an angle that facilitates stapler wedge resection. Compared to previous methods, 713 our strategy does not need special devices; only a 0 suture and a sponge, widely available. Yet, as the suture traction is not accommodated within a uniportal incision, it does not interfere with the movement of other surgical devices inside or outside the thoracic cavity, facilitating handling and resection of the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transthoracic thoracoscopic surgery is the most commonly employed approach to the thoracic cavity. Liu CC [4] reported that they had performed a case of thoracoscopic lobectomy through the subxiphoid approach as an access to the chest for a patient with lung cancer in the left upper lobe. Recently, Hernandez-Arenas reported their initial experience of 153 consecutive patients with uniportal, video-assisted, subxiphoid approach to major lung resection [7].…”
Section: Discussionmentioning
confidence: 99%
“…Recently Tsuboshima et al (12) described good results using a technique called modified Chest Wall Pulley (mPulLE) for Lung Excision. In their approach the lung is suspended using a kind of pulley through a single incision.…”
Section: Discussionmentioning
confidence: 99%